Effect of Partial Replacement of Wheat Flour with Various Mangrove Fruit Flours and Different Emulsifiers on Physicochemical Properties of Biscuits - Jariyah, Jariyah; Yektiningsih, Endang; Sarofa, Ulya; Sopadeo, Peter Adeye (Indonesian Journal of Agricultural Research, 2018)
Biscuit formulation was produced from the partial substitution of wheat flour using mangrove fruit flour (MFF) with the addition of an emulsifier. In this study, Pedada (Sonneratia caseolaris) and Lindur (Bruguiera ghymnorhiza) were used as two varieties of MFF. Lecithin and sodium stearoyl lactylate (SSL) was used to enhance the physical properties of the biscuits. An experiment was conducted by replacing wheat flour with MFF at different levels (0%, 20%, and 30%). Margarine, sugars, eggs, glucose syrups, and emulsifiers were added after mixing wheat flour with MFF, baking powder, and milk powder uniformly. Dough sheets were formed and baked on a greased tray at 1500C for 10 to 15 min. The biscuits produced were analyzed for spread ratio, breaking strength, and color (L*, a*, and b*), ranging from 4.13–5.07; 54.07–89.77 N; and 34.70–50.90 L*, 15.17–18.80 a*, and 12.00–28.07 b*, respectively. The analysis of chemical composition showed that the carbohydrate ranged from 90.99–93.60%, protein 4.26–7.12%, fat 0.22–0.59%, ash 0.93–1.75%, and moisture 0.88–1.36%, and the energy value spanned over 391.10–395.33 cal/100 g. Sensory evaluation rating, substitution of 20% with MFF, and SSL addition had the highest acceptability compared to other formulations.